2005
DOI: 10.1159/000087783
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Response and Well-Being in Pre-, Peri- and Postmenopausal Women with Major Depressive Disorder Treated with Fluoxetine

Abstract: Background: We assessed the impact of menopausal status on treatment response and well-being in a cohort of outpatient women with major depressive disorder (DSM-III-R criteria), who received treatment with fluoxetine (20 mg/day for 8 weeks). Methods: Menopausal status was defined based on age, presence of menstrual irregularity or amenorrhea and vasomotor symptoms. Remission and response of depression were defined as a 17-item Hamilton Depression Rating Scale (HAM-D-17) score ≤7 and a HAM-D-17 decrease ≧50%, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
2
14
1
Order By: Relevance
“…No difference between younger and older women Desipramine (85) 156 No significant differences although there was a trend for better response in older women Venlafaxine, SSRIs (81) 2045 Venlafaxine was more efficacious than SSRIs in younger and older women TCA's, fluoxetine (68) 1746 Fluoxetine -no significant difference in younger or older women Fluoxetine (86) 184…”
Section: Gender and Treatment Interactionmentioning
confidence: 99%
“…No difference between younger and older women Desipramine (85) 156 No significant differences although there was a trend for better response in older women Venlafaxine, SSRIs (81) 2045 Venlafaxine was more efficacious than SSRIs in younger and older women TCA's, fluoxetine (68) 1746 Fluoxetine -no significant difference in younger or older women Fluoxetine (86) 184…”
Section: Gender and Treatment Interactionmentioning
confidence: 99%
“…Most studies reported that postmenopausal women appear to be more commonly nonrespondive to serotonergic antidepressant therapy than younger women [150][151][152][153][154], although not systematically [155,156]. Some studies have investigated the possible effect of estrogen as an adjunct treatment for postmenopausal depression.…”
Section: The Use Of Hormonal Therapies In Clinical Practicementioning
confidence: 99%
“…Because differential gender responses to antidepressant medications are reported in the literature, 12,13 several investigators have also examined whether reproductive status itself influences responsiveness to antidepressant medication, with most using age cutoffs as proxies for postmenopausal identification (age thresholds varying from 45 to 56). 12,[14][15][16][17] Findings are mixed, with some study teams reporting differential response rates to classes of antidepressants between premenopausal and postmenopausal women. 12,14,18,19 Specifically, Harvey et al 19 found in a clinical trial comparing imipramine with sertraline that premenopausal women experienced depressive symptom deterioration at a greater proportion of their visits than did postmenopausal women (8.6% vs. 4.5%, p < 0.01) or men (5.9%, p < 0.01).…”
Section: Introductionmentioning
confidence: 99%
“…14 However, others have failed to confirm such age-related differences in psychotropic treatment response. 15,17 In studies of psychotherapy, gender has not been a consistent predictor of outcome, although most study designs are limited by differential dropout rates, small sample sizes, or small numbers of male participants. 20,21 To our knowledge, there have been no investigations of potential influences of reproductive status on women's response to psychotherapy.…”
Section: Introductionmentioning
confidence: 99%